Diagnostic and therapeutic challenges in managing persistent air leaks - Revelo, Alberto; Keshishyan, Sevak; Epelbaum, Oleg; Yaghoubian, Saman; DeLorenzo, Lawrence; Chandy, Dipak; Carroll, Francis; Paul, Lisa; Harris, Kassem (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Persistent air leak (PAL) is a common and challenging condition associated with increased morbidity and mortality, intensive care unit admission, and prolonged hospital stay. Multiple medical and surgical approaches have been developed to manage PAL. Depending on the etiology of PAL, surgical management may be effective and usually performed using video-assisted thoracoscopic surgery (VATS). Medical management is less invasive and consists of pleural or bronchoscopic methods. The non-surgical techniques for the management of PAL have not been investigated in large prospective studies, and so their use is mostly guided by observational data. Specifically, the role of intrabronchial valve (IBV) placement for PAL has been the subject of an ever-increasing number of case reports and series documenting successful deployment of IBVs for both surgical and medical PAL. In this case-based discussion, we describe three patients with non-surgical PAL who were managed using multiple modalities, including both surgical and medical approaches. These cases illustrate the challenges in identifying the location of the air leak and in the application of various therapeutic options.